2010
DOI: 10.1016/j.virol.2010.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of HIV-1 to cells expressing rhesus monkey TRIM5α

Abstract: The cross-species transmission of retroviruses is limited by host restriction factors that exhibit inter-species diversity. For example, the TRIM5α proteins of Old World monkeys block the early, post-entry steps in human immunodeficiency virus (HIV-1) infection. We adapted an HIV-1 isolate to replicate in cells expressing TRIM5αrh from rhesus monkeys, an Old World species. A single amino acid change in the cyclophilin-binding loop of the HIV-1 capsid protein allowed virus replication in cells expressing TRIM5α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 66 publications
(107 reference statements)
3
30
0
Order By: Relevance
“…These would include the CA N-terminal beta hairpin loop, a region C-terminal to helix 4, and the surfaceexposed N-terminal end of helix 6. A similar conclusion has been reached from studies of different lentiviruses (38)(39)(40)(41)(42). Such an extended interaction domain would be consistent with structural studies of the TRIM5␣ PRY-SPRY region that suggest a large, triangular surface region containing the specificity determinants of restriction (25,43,44).…”
Section: Discussionsupporting
confidence: 83%
“…These would include the CA N-terminal beta hairpin loop, a region C-terminal to helix 4, and the surfaceexposed N-terminal end of helix 6. A similar conclusion has been reached from studies of different lentiviruses (38)(39)(40)(41)(42). Such an extended interaction domain would be consistent with structural studies of the TRIM5␣ PRY-SPRY region that suggest a large, triangular surface region containing the specificity determinants of restriction (25,43,44).…”
Section: Discussionsupporting
confidence: 83%
“…4A and Fig. S4), including the β1/β2 hairpin, L5/6, and L4/5 regions in HIV CA and the corresponding sites on MLV CA (30,33,(45)(46)(47)(48)(49)(50). Specifically, TRIM5α V1 may interact with CA β1/β2 at the center of the CA hexamer, as swapping the V1 region of rhTRIM5α and huTRIM5α resulted in a change of the restriction specificity toward MLV CA with mutations in the β1/β2 region (30).…”
Section: Discussionmentioning
confidence: 99%
“…S5) (17, 18). The most likely scenario is that an extended V1 latches onto the binding surface on one CA molecule, as it has been implicated in interaction with β1/β2 (30) and residue 110 of MLV CA (corresponding to the L5/6 region in HIV CA) (47), whereas V2 and V3 interact with CA molecules in a neighboring hexamer (Fig. 4 D and E).…”
Section: Discussionmentioning
confidence: 99%
“…We also constructed another two strains (designated 86M116E and 86E116E) encoding distinct substitutions at V86. A previous study had shown that V86M CA allows HIV-1 to grow in HeLa-CD4 cells expressing Rh TRIM5a (Pacheco et al, 2010); separate work revealed that the V86E mutant exhibits decreased sensitivity to restriction by the Rh TRIM5a (Soll et al, 2013). When we compared the growth of all three V86 mutants in the presence of CM TRIM5a, 86A116E grew to higher titres in the presence of CM TRIM5a than 86E116E (Fig.…”
Section: Ipmentioning
confidence: 83%